2013
DOI: 10.1097/opx.0b013e318288d19c
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront-Guided Scleral Lens Prosthetic Device for Keratoconus

Abstract: Purpose To investigate the feasibility of correcting ocular higher order aberrations (HOA) in keratoconus (KC) using wavefront-guided optics in a scleral lens prosthetic device (SLPD). Methods Six advanced keratoconus patients (11 eyes) were fitted with a SLPD with conventional spherical optics. A custom-made Shack-Hartmann wavefront sensor was used to measure aberrations through a dilated pupil wearing the SLPD. The position of SLPD, i.e. horizontal and vertical decentration relative to the pupil and rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 33 publications
8
83
2
2
Order By: Relevance
“…While the gains in acuity compared to habitual correction are substantial, all 10 study eyes have poorer VA compared with age-matched normal levels, even though residual higher-order aberrations are within 1 SD of normal mean values. This is in agreement with prior reports by Sabesan et al 26 …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…While the gains in acuity compared to habitual correction are substantial, all 10 study eyes have poorer VA compared with age-matched normal levels, even though residual higher-order aberrations are within 1 SD of normal mean values. This is in agreement with prior reports by Sabesan et al 26 …”
Section: Resultssupporting
confidence: 94%
“…26 They also noted that while improved, visual performance did not reach levels seen in individuals that habitually experience normal levels of higher-order aberration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we outline the literature that has demonstrated the limitations associated with aberration-controlled soft contact lens designs and the need for further work to validate the clinical feasibility of such modalities for the management of keratoconus. Although still currently limited to the research domain and not yet directly applicable to managing patients in clinical practice, we agree with the sentiment that customised aberration-controlled scleral lenses 2,3 show promise as a potential future vision-correction platform for keratoconus. In a small population of seven individuals with keratoconus, Marsack and colleagues 2 have shown that wave-front guided scleral contact lenses can optically compensate for higher-order aberrations; however, as these authors note, 2 a range of factors will need to be surmounted in order for the custom correction of highly aberrated eyes to achieve clinical translation.…”
Section: Editorsupporting
confidence: 56%
“…To overcome this limitation, wavefront-guided customized scleral lens may be a good option. Sabesan et al 31 reported the SD of the movement for scleral lenses designed specifically for stability (measured over a brief 20-second test window) as T54.5 Km (vector movement in x and y) and a rotation of T0.58 degrees, which is much smaller than that of soft contact lenses. In the study by Sabesan et al, 31 the customized scleral lens prosthetic device corrected the HOA of advanced keratoconic patients to normal levels and significantly improved their vision.…”
Section: Discussionmentioning
confidence: 98%